INNOVATIVE DEVELOPMENT TENDENCIES IN OUR COUNTRY BASED ON WORLD EXPERIENCE - Khujamberdiyev T.; Pardaeva B. U.; Davranova G. N. (American Journals Publishing, 2025)
In Uzbekistan, many types of activities are involved in conducting research on the theories, formation and opportunities of innovative development in ensuring the growth of the national economy. This article presents a number of practical examples of developed countries forming their national innovation systems and taking high places in the global innovation index.
Keywords: Global innovation index, innovative development, national innovation system, economic system, new technologies.